Camera and telemetry data from Slovak roads in various light and weather conditions - Marek Galinski; Tomáš Milesich; Matej Janeba; Ján Danko; Peter Lehoczký; Ľuboš Magdolen; Lukáš Šoltés; Adam Tomčala (Scientific Data)
Abstract In this paper, we describe the dataset captured with our proprietary data capture solution mounted on top of a Land Rover Defender vehicle. The captured data are the real data of drives on various Slovak roads. The total dataset consist of almost 33 hours of driving with a automotive grade FPD Link camera with 30 fps and with additional sensors such as high-precision GNSS sensor and modem towards mobile data connectivity LTE and 5 G. There are various road types and weather and conditions. Road types are 2-lane highway, 3-lane highway, urban environment, 1st class road (main, national), 2nd class road (main, regional), 3rd class road (local). Weather and light conditions are direct sunlight, normal daylight, rain/fog and dawn/twilight. All frames have captured its position, velocity, heading and connectivity information.